2022
DOI: 10.1155/2022/7981325
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Frequency of ABO and Rhesus (D) Blood Groups in Somalia: A Retrospective Study on Students of Jazeera University, Mogadishu‐Somalia

Abstract: Background. There are differences in the distribution and frequency of ABO and D blood groups in different populations of the world. Relatively very little information is available about blood group distributions in the Somali population. Objectives: To identify the distribution and frequency of ABO and D blood groups among the Somali people. Methods. A retrospective cross-sectional study of 1811 enrolled students of Jazeera University was conducted in Jazeera University diagnosis and research center, Mogadish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…Our study revealed the most prevalent blood group in surgical patients at the Rivers State University Teaching Hospital as blood group O (63.0%). this was in agreement with the study done by Mohamed A et al in Somalia, which showed that blood group O was the most common, this comprised of 61% of the total blood group a little lower than what was shown in our study [1]. The distribution of blood group from our study showed that O blood group was the most prevalent (63%) followed by A (17.8%), B (15.1%) and AB (4.1%) (tables 1 and 2).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our study revealed the most prevalent blood group in surgical patients at the Rivers State University Teaching Hospital as blood group O (63.0%). this was in agreement with the study done by Mohamed A et al in Somalia, which showed that blood group O was the most common, this comprised of 61% of the total blood group a little lower than what was shown in our study [1]. The distribution of blood group from our study showed that O blood group was the most prevalent (63%) followed by A (17.8%), B (15.1%) and AB (4.1%) (tables 1 and 2).…”
Section: Discussionsupporting
confidence: 94%
“…There are differences in the distribution and frequency of ABO and D blood groups locally and globally [1,2]. These differences in ABO is also applicable among surgical patients worldwide [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations